Safety and efficacy of endoscopic sleeve gastroplasty for obesity management in new bariatric endoscopy programs: a multicenter international study. (June 2022) - Sarkar, Avik; Tawadros, Augustine; Andalib, Iman; Shahid, Haroon M.; Tyberg, Amy; Alkhiari, Resheed; Gaidhane, Monica; Kedia, Prashant; John, Elizabeth S.; Bushe, Bryce; Martinez, Guadalupe Ma; Zamarripa, Felipe; et al.
Background: Endoscopic sleeve gastroplasty (ESG) is an incisionless procedure that reduces the size of the gastric cavity. In prior studies, it has been proven to be a safe and effective treatment for obesity. In this study, we performed a collaborative study to evaluate the effectiveness of ESG among new endobariatric programs. Methods: This was an international, multicenter study reviewing the outcomes of ESG in centers starting ESG programs. Total body weight loss, change of body mass index (BMI), excess body weight loss (EBWL), technical success, duration of hospitalization, and immediate and delayed adverse events and complications at 24 h, 1 week, and 1, 3, and 6 months post-procedure were evaluated. Results: A total of 91 patients (35 males) from six centers were included. The patients' mean BMI before the procedure was 38.7 kg/m 2 . BMI reduction at 3 months was 7.3 ( p  < 0.000), at 6 months 9.3 ( p  < 0.000), and at 12 months 8.6 ( p  < 0.000) from baseline. EBWL was 17.3% at 1 month ( p  < 0.000), 29.2% at 3 months ( p  < 0.000), and 35.6% at 6 months ( p  < 0.000). The mean procedure duration was 85.1 min. The mean length of hospital stay post-procedure was 27 h. Conclusion: ESG provides EBWL percentage sustained up to 12 months. These results are equivalent among the new ESG centers compared to previous studies by expert centers. Lay title: Endoscopic sleeve gastroplasty in new bariatric endoscopy programs: Plain Language Summary: This article is the result of a collaborative international study on new endoscopic programs offering endoscopic sleeve gastroplasty. The minimally invasiveness and increasing accessibility of this technique makes it very attractive for patients with obesity while being poor candidate for surgery or refusing surgery. This study will also provide valuable information regarding this rising technique of endobariatric treatment.